2018
DOI: 10.1038/s41598-018-23339-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic homogeneity of the invasive lionfish across the Northwestern Atlantic and the Gulf of Mexico based on Single Nucleotide Polymorphisms

Abstract: Despite the devastating impact of the lionfish (Pterois volitans) invasion on NW Atlantic ecosystems, little genetic information about the invasion process is available. We applied Genotyping by Sequencing techniques to identify 1,220 single nucleotide polymorphic sites (SNPs) from 162 lionfish samples collected between 2013 and 2015 from two areas chronologically identified as the first and last invaded areas in US waters: the east coast of Florida and the Gulf of Mexico. We used population genomic analyses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 72 publications
6
26
1
Order By: Relevance
“…The PCA and F ST analyses of RAD‐seq data presented here, rather, indicate that there is no structure. These findings are similar to those presented in Pérez‐Portela et al () for the Gulf of Mexico. Unfortunately, data reported in Pérez‐Portela et al () were generated using a different restriction enzyme than we used, precluding a direct side‐by‐side analysis of results.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The PCA and F ST analyses of RAD‐seq data presented here, rather, indicate that there is no structure. These findings are similar to those presented in Pérez‐Portela et al () for the Gulf of Mexico. Unfortunately, data reported in Pérez‐Portela et al () were generated using a different restriction enzyme than we used, precluding a direct side‐by‐side analysis of results.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are similar to those presented in Pérez‐Portela et al () for the Gulf of Mexico. Unfortunately, data reported in Pérez‐Portela et al () were generated using a different restriction enzyme than we used, precluding a direct side‐by‐side analysis of results. The results of both this study and Pérez‐Portela et al () indicate that it is possible that previously reported evidence of population structure among basins seen in mtDNA data could be solely driven by the absence of certain mitochondrial alleles in certain ocean basins.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations